Pesquisa e desenvolvimento de vitrocerâmicos de alta resistência ao impacto - Brosler, Priscilla Oliveira [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
Glass-ceramics associate high performance with ease of manufacture, since they can be formed like glass and have the mechanical properties of a crystalline ceramic. For the present study, the glass-ceramic system used as a base was the LAS (Lithium-Aluminium-Silicate) system with the addition of zirconium oxide (ZrO2) and titanium oxide (TiO2) as nucleating agents. The main objective was to research and develop glass-ceramics with high mechanical strength for application in ballistic shielding. The stages of the study consisted of formulation and melting of the base glass, followed by annealing and heat treatment to obtain the glass-ceramics. Subsequently, the samples were subjected to materiolographic preparation, Vickers microhardness testing, X-ray diffraction (DRX), differential scanning calorimetry (DSC), fracture toughness determination (KIC), crystalline phase quantification using the Rietveld method and finally, ballistic testing. Heat treatments with long time nucleation and crystallization resulted in glass-ceramics with microhardness results higher than 10 GPa. The results of the ballistic tests have proven that the studied glass-ceramics are strong candidates for ballistic applications due to their excellent performance

Vitrocerâmicas associam alto desempenho com facilidade de manufatura, pois podem ser conformadas como se fossem vidros, associada às propriedades mecânicas dos materiais cerâmicos cristalinos. Neste trabalho, foi utilizado como base o sistema LAS (Lítio-AluminoSilicato), com nucleação a partir de óxido de zircônio (ZrO2) e óxido de titânio (TiO2). Teve-se como objetivo pesquisar e desenvolver vitrocerâmicas de alta resistência mecânica para aplicação em blindagem balística. As etapas foram: formulação e fusão dos vidros, seguida por recozimento e tratamento térmico para obtenção das vitrocerâmicas. Posteriormente, foi feita a preparação materiolográfica das amostras, medidas de microdureza Vickers, difração de raiosX, análise térmica (DSC), determinação da tenacidade à fratura (KIC), quantificação de fases cristalinas através do método de Rietveld e ensaio balístico. Tratamentos térmicos com longos patamares de nucleação e de cristalização resultaram em vitrocerâmicas com microdureza acima de 10 GPa. Através dos ensaios balísticos, foi comprovado que as vitrocerâmicas estudadas são fortes candidatas a aplicações balísticas, devido ao excelente desempenho apresentado
Research and development of glass-ceramics of high impact resistance
Keywords: Material cerâmico; Cerâmica; Lítio; Microscopia; Cristalização; Ceramic materials